THE ROLE OF ARTIFICIAL INTELLIGENCE IN EDUCATION - G’ulomalieva Umida (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article explores the role of artificial intelligence (AI) in education and how it is changing the learning process in schools and universities. It explains how AI supports both students and teachers, provides examples of its use in real-life educational settings, and discusses both benefits and challenges. The article also highlights why understanding AI is important for students who want to succeed in a modern digital world.